HUBUNGAN DEBU, KEBISINGAN DAN KARAKTERISTIK INDIVIDU DENGAN KESEHATAN MASYARAKAT TERDAMPAK AKTIFITAS PT BUMI INDAH DI DESA PENFUI TIMUR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Laurensius Talan; Anderias Umbu Roga; Yacob M. Ratu (Jurnal Health Sains, 2022)
Industrialization helps meet human needs quickly and can harm human health if not properly monitored. The people of East Penfui Village feel the impact of PT Bumi Indah's activities in the form of dust and noise. This study aims to determine the relationship between dust and noise with the incidence of acute respiratory infection and hearing loss. This research is a quantitative research with a cross sectional approach. The study population consisted of 40 employees of PT Bumi Indah and 171 affected communities. The sample consisted of 30 employees of PT Bumi Indah and 30 other affected communities who were determined using a purposive sampling technique. Data were obtained through surveys, interviews and measurement with tools. Data were analyzed by univariate, bivariate and multivariate. The results showed that there was a relationship between dust and acute respiratory infection  (p = 0.003) and OR = 5.5, meaning that the risk of acute respiratory infection illness in people exposed to dust that did not meet the requirements was 5.5 times greater than people who were not exposed to dust that did not meet the requirements. . There is a relationship between age and the incidence of acute respiratory infection (p = 0.030) and OR = 9.0, meaning that the incidence of acute respiratory infection in people aged 35 years or more is 9.0 times greater than in people under 35 years of age. There is a relationship between length of exposure to hearing loss (p=0.0001) and OR=12.0, meaning that the risk of hearing loss in people exposed for 5 years or more is 12.0 times greater than in people exposed for less than 5 years. There is a relationship between age and hearing loss (p = 0.019) and OR = 4.2, meaning that the risk of hearing loss in people aged 35 years or over is 4.2 times greater than in people under 35 years of age. The most dominant risk factor for the incidence of acute respiratory infection in communities affected by PT Bumi Indah's activities is the length of exposure with p = 0.0001 and OR = 8.32. The most dominant risk factor for hearing loss in the community affected by PT Bumi Indah's activities is the length of exposure with p = 0.0001 and OR = 21.54. It is suggested to PT Bumi Indah to provide personal protective equipment for workers, routinely watering the roads traversed by the company's vehicles, closing the trunk of the truck when loading materials, making portals at a certain distance to reduce vehicle noise.